Exploring the Relationship Between Initial Mathematics Skill and a Kindergarten Mathematics Intervention. (January 2019) - Clarke, Ben; Doabler, Christian T.; Smolkowski, Keith; Turtura, Jessica; Kosty, Derek; Kurtz-Nelson, Evangeline; Fien, Hank; Baker, Scott K.
This study examined the role of initial skill in moderating intervention effects of a 50-lesson mathematics intervention program, ROOTS, for at-risk kindergarten students focused on developing whole-number concepts and skills. The study utilized a randomized block design with at-risk students ( n = 592) within classrooms ( n = 60) randomly assigned to one of two treatment conditions (a small group of two to five students) or control condition. Proximal and distal measures were collected in the fall (pretest), spring (posttest), and winter of first grade (delayed posttest). Analyses examined the moderating effects of initial student achievement level on mathematics outcomes. Results indicated that initial skill moderated student outcomes but the relationship did not differ by group size. Implications for tiered mathematics instruction are discussed.